2021
DOI: 10.1101/2021.03.25.21253694
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

From classic to rap: Airborne transmission of different singing styles, with respect to risk assessment of a SARS-CoV-2 infection

Abstract: Since the Covid-19 virus spreads through airborne transmission, questions concerning the risk of spreading infectious droplets during singing and music making arose. To contribute to this question and to help clarify the possible risks, we analyzed 15 singing scenarios (1) qualitative, by making airflows visible, while singing, and (2) quantitative, by measuring air velocities in three distances (1m, 1.5m and 2m). Air movements were considered positive, when lying above 0.1 m/s, which is the usual room air ve… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 19 publications
0
3
0
Order By: Relevance
“…A preprint study of 3 professional singers found a maximum singing velocity of 0.7 m s –1 . 36 Giovanni et al found that air velocity varied from 0.28 to 1.8 m s –1 depending on the vocal exercise that was performed. 37 The velocity for singing from this study was lower than what was found by Chao et al for talking and coughing (3.9 and 11.7 m s –1 respectively).…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…A preprint study of 3 professional singers found a maximum singing velocity of 0.7 m s –1 . 36 Giovanni et al found that air velocity varied from 0.28 to 1.8 m s –1 depending on the vocal exercise that was performed. 37 The velocity for singing from this study was lower than what was found by Chao et al for talking and coughing (3.9 and 11.7 m s –1 respectively).…”
Section: Resultsmentioning
confidence: 99%
“…This finding is comparable to previous studies. A preprint study of 3 professional singers found a maximum singing velocity of 0.7 m s –1 . Giovanni et al found that air velocity varied from 0.28 to 1.8 m s –1 depending on the vocal exercise that was performed .…”
Section: Resultsmentioning
confidence: 99%
“…A preprint study of 3 professional singers found a maximum singing velocity of 0.7 m/s. 36 Giovanni et al (2020) found that air velocity varied from 0.28 m/s to 1.8 m/s depending on the vocal exercise that was performed. 37 The velocity for singing from this study was lower than what was found by Chao et al (2009) for talking and coughing (3.9 m/s and 11.7 m/s respectively).…”
Section: Flow Characterizationmentioning
confidence: 99%